Flos potentia - Mazlan, Amirul Aiman; Hamizad, Muhammad Azhad; Wan Mohd Nazar Noor, Wan Muhammad Shafiq; Mohamed, Nurul Najidah; Zamri, Siti Norziahidayu Amzee (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
Flowers are always regarded as a symbol of love, beauty and gift of nature. People often use flowers to portray their feelings and happiness. In such events like weddings, graduations, and valentine’s day, people express their appreciations towards loved ones with bouquet of fresh flowers. However, these flower bouquets only last for a certain period of time. Therefore, a product named Flos Potentia is introduced to preserve the freshness of the flowers and make them last longer. The list of ingredients tested to make this product are water, paracetamol, glycerine, eggshells and distilled water. The eggshells are boiled and extracted by using distilled water which produced a new solution called hyaluronic acid. Therefore, there are two main solutions considered to preserve the freshness of the fresh flowers which are glycerine and hyaluronic acid. Next, five containers of constant size are used to place the flowers with the solutions, where these five different solutions are tested to get the best results. The experiment took about two to three weeks where the best preservation for the flowers turns out to be the handmade hyaluronic acid, followed by glycerine with boiled water, glycerine with warm water, paracetamol with water, and lastly, water.